Outdoor Learning Activities in Early Childhood Education: Exploring Benefits and Challenges Through Bibliometric Analysis - Nice Maylani Asril; Ni Wayan Surya Mahayanti; Ni Komang Arie Suwastini; I Wayan Artanayasa; Yukiko Masumoto; Fumiko Kagiura (Journal of Sport Science and Education, 2024)
Despite the growing recognition of positive effects on children's physical, cognitive, social and emotional development through outdoor learning within early childhood education (ECE), these practices are inconsistently integrated into ECE curricula. Current study analyses bibliometric research to explore the trend in fitness training and highlights pertinent authors who conducted valuable research on this issue. Through DimensionAI system, 43 publications were found using “outdoor learning” AND "early childhood" in Titles and Abstracts fields; Among them: After the application of inclusion criteria for OA (open access) articles by English language indexed also ownership as an open repository through Dimensions we selected a total number n =18 articles which had been published between years from 2015 to date. Based on Microsoft Excel, VOSviewer was employed to construct the co-authorship networks of authors and characterize patterns in terms of citation or between subfields. Analysis indicates a marked increase in research activity over the last few years, which is reflective of an increased interest in outdoor learning. At the same time, it identifies limitations such a focus on as minority of scholars influencing outdoor learning research and limited incorporation into larger educational frameworks. More research is needed on practical challenges and for this generation, in resource-constrained settings. These results also underscore the need to broaden both representation within research and practical approaches of outdoor early education. Findings from the study of research provide a snapshot on what we know and do not know, as well promising directions for researchers to continue with their work in order to help reduce inequity.